2022
DOI: 10.3390/ijms23094964
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ATF3 in Neuronal Differentiation and Development of Neuronal Networks in Opossum Postnatal Cortical Cultures

Abstract: Activating transcription factor 3 (ATF3), a member of the ATF/cAMP response element-binding (CREB) family, is upregulated by various intracellular and extracellular signals such as injury and signals related to cell proliferation. ATF3 also belongs to the regeneration-associated genes (RAG) group of transcription factors. RAG and ATF/CREB transcription factors that play an important role in embryonic neuronal development and PNS regeneration may also be involved in postnatal neuronal differentiation and develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…It is involved in the complex process of cellular stress response. A latest study indicated that ATF3 was involved in neuronal differentiation and 14 Oxidative Medicine and Cellular Longevity development of neuronal networks in opossum postnatal cortical cultures [27]. Sesn2, sestrin2, is a highly conserved antioxidative protein which was activated in various stress [28].…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in the complex process of cellular stress response. A latest study indicated that ATF3 was involved in neuronal differentiation and 14 Oxidative Medicine and Cellular Longevity development of neuronal networks in opossum postnatal cortical cultures [27]. Sesn2, sestrin2, is a highly conserved antioxidative protein which was activated in various stress [28].…”
Section: Discussionmentioning
confidence: 99%
“…The template was laid under the culture plate to control the strength and speed of the scratch. Under direct vision, the sterile surgical blade was used to cut along the line of the template to damage the neurons and make the neuron scratch damage model 30,31 …”
Section: Methodsmentioning
confidence: 99%
“…Under direct vision, the sterile surgical blade was used to cut along the line of the template to damage the neurons and make the neuron scratch damage model. 30 , 31 …”
Section: Methodsmentioning
confidence: 99%
“…MAP2K1 was identified in both P5 and P18 opossums, with higher expression in P18 (1.08 times more). We have recently shown [ 105 ] that both MAPK/p38 and JNK/c-Jun signaling pathways are involved during neurite outgrowth and neuronal network formation as well as during regeneration after injury through the interaction and induction of activating transcription factor 3 (ATF3) [ 106 , 107 ].…”
Section: Nek1 and Cfap410 And Interacting/related Partnersmentioning
confidence: 99%